Topical treatment of actinic keratoses in organ transplant recipients: a feasibility study for SPOT (Squamous cell carcinoma Prevention in Organ transplant recipients using Topical treatments). (1st September 2022) - Hasan, Zeeshaan‐Ul; Ahmed, Ikhlaaq; Matin, Rubeta N.; Homer, Victoria; Lear, John T.; Ismail, Ferina; Whitmarsh, Tristan; Green, Adele C.; Thomson, Jason; Milligan, Alan; Hogan, Sarah; Van‐de‐Velde, Vanessa; et al.
Abstract: Background: The risk of cutaneous squamous cell carcinoma (cSCC) is significantly increased in organ transplant recipients (OTRs). Clearance of actinic keratoses (AKs) is generally regarded as a surrogate biomarker for cSCC prevention. OTR‐cSCC chemoprevention with topical AK treatments has not been investigated in randomized controlled trials (RCTs), although there is evidence that 5% 5‐fluorouracil (5‐FU) may be chemoprotective in immunocompetent patients. Objectives: To assess the feasibility, activity and evaluation outcomes relevant to the design of a future phase III RCT of topical cSCC chemoprevention in OTRs. Methods: OTRs with 10 or more AKs in predefined areas were randomized 1 : 1 : 1 to topical 5‐FU, 5% imiquimod (IMIQ) or sunscreen (sun‐protective factor 30+) in a phase II, open‐label RCT over 15 months. Feasibility outcomes included proportions of eligible OTRs randomized, completing treatment and willing to be re‐treated. AK activity [AK clearance, new AK development, patient‐centred outcomes (toxicity, health‐related quality of life, HRQoL)] and evaluation methodology (clinical vs. photographic) were assessed. Results: Forty OTRs with 903 AKs were randomized. All feasibility outcomes were met (56% of eligible OTRs were randomized; 89% completed treatment; 81% were willing to be re‐treated). AK activity analyses found 5‐FU and IMIQ were superior to sunscreen for AK clearance and prevention of new AKs. 5‐FU was more effective than IMIQ in AK clearance and prevention in exploratory analyses. Although toxicity was greater with 5‐FU, HRQoL outcomes were similar. Conclusions: Trials of topical AK treatments in OTRs for cSCC chemoprevention are feasible and AK activity results support further investigation of 5‐FU‐based treatments in future phase III trials. What is already known about this topic? Cutaneous squamous cell carcinoma (cSCC) is significantly more common in immunocompromised individuals including organ transplant recipients (OTRs) compared with immunocompetent populations. cSCC chemoprevention activity of sunscreen and 5‐fluorouracil‐based (5‐FU) actinic keratosis (AK) treatments has been demonstrated in randomized controlled trials (RCTs) in immunocompetent populations but not in OTRs. AKs are cSCC precursors and their clearance and prevention are generally regarded as surrogate endpoint biomarkers for potential cSCC chemoprevention activity. What does this study add? SPOT (SCC Prevention in OTRs using Topical treatments) has confirmed that RCTs of OTR‐cSCC chemoprevention with topical AK treatments are feasible. It also suggests that topical 5‐FU may be superior to 5% imiquimod and sunscreen in AK clearance and prevention. Together with recent evidence from several RCTs in the general population, these data provide a compelling rationale for further studies of intervention with 5‐FU‐based topical chemoprevention approaches in OTR‐cSCC prevention. Abstract: Clearance of actinic keratoses (AK) is generally regarded as a surrogate biomarker for CSCC prevention. Our aim is to assess feasibility, activity and evaluation outcomes relevant to design of a future phase III RCT of topical CSCC chemoprevention in OTRs. We have concluded that trials of topical AK treatments in OTRs for CSCC chemoprevention are feasible and AK activity results support further investigation of 5‐FU‐based treatments in future phase III trials. Linked Comment: M. Samimi. Br J Dermatol 2022; 187 :281–282.